(untitled) (Bangladesh Journal of Agriculture, 2022)
Mangrove apple (Sonneratia caseolaris) is a widespread underutilized fruit species of coastal region of Bangladesh. The present study was undertaken to find out the flowering, fruiting, nutritional quality and extent of variability among different mangrove apple germplasm. Twelve germplasm were selected from three locations - six (SC 02, SC 03, SC 04, SC 05, SC O6 and SC 07) from Dumki sadar, two (SC 01 and SC 08) from PSTU germplasm centre and four (SC 09, SC 10, SC 11 and SC 12) from Patabuniya, Dumki, Patuakhali. Flowering season started from May and continued up to November. Percentage of fruit setting ranged from 96.03 to 89.96% in SC 01 and SC 12, respectively. Required time for fruit maturation ranged from 106 days (SC 06) to 55 days (SC 05). Single fruit weight varied from 122.3 g (SC 01) to 54.33 g (SC 04). The length and diameter of fruit ranged from 2.9 cm (SC 05) to 2.20 cm (SC 07) and 5.20 cm (SC 05) to 3.60 cm (SC 04), respectively. The maximum edible portion (66.15%) was recorded in SC 01, and it was the lowest (51.45%) in SC 07. Chemical analysis was done with the pulp of selected germplasm where the germplasm SC 01 exhibited the best performance in all parameters of chemical analysis. This analysis was performed at four different ripening stages. The highest TSS (8.72%) was recorded in stage I. The highest pH level (3.51) was observed in stage III and the lowest pH level (2.83) was found in stage I. The highest ascorbic acid content (37.50 mg/100g) was noted in stage IV. Flower of mangrove apple produces a kind of honey. Fresh fruits and seeds have high nutritional and medicinal value. Wood of this plants provides great livelihood support to the local residents for fetching good price in the markets. Proper utilization of S. caseolaris may contributes the nutritional security of the women and children of this area by fulfilling the demand for micronutrients, especially vitamin C. Bangladesh J. Agri. 2019-2021, 44-46: 9-17